THE INDUSTRY AND HIGHER EDUCATION INSTITUTIONS (HEIS) COOPERATION IN IMPROVING THE MARKETABILITY OF TECHNICAL STREAM STUDENTS - Siti Nur Amirah Md Jamain; Nurul Aini Mohd. Ahyan; Hanifah Jambari; Nur Hazirah Noh@Seth; Mohamad Rasidi Pairan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Marketability skills of technical students can be enhanced by fostering a strong cooperation between the industry and educational institutions. Therefore, this study was conducted to examine the roles played by the industry and Higher Education Institutions (HEIs) in increasing the marketability of technical students. This study was conducted to achieve two main objectives, first, to identify the role of HEIs in improving the quality of their curriculum and second, to identify the role of the industry in improving students’ performance during industrial training. This quantitative study involved 25 CISEC officers and lecturers of polytechnics across Johor and 210 students enrolled in the mechanical engineering programme at the same polytechnics who are undergoing industrial training. The mean value obtained from the analysis using Statistical Package for Social Science (SPSS) version 26.0 indicate that HEIs play a role in balancing the curriculum content, develop generic skills, and cultivating science and technology in teaching. Meanwhile, the industry plays a very important role in increasing graduates’ marketability skills, specifically in terms of their self-skills, knowledge, and personal attributes during industrial training. The finding indicates there is an-going collaboration between the industry and HEIs in improving the marketability of technical stream students. Therefore, the Vocational Training and Technical Education Division should encourage various industrial sectors to collaborate with HEIs ensure to increase marketability of technical stream graduates.